Dental management of patients with renal diseases or undergoing renal transplant - Hamad Albagieh; Asim Alosimi; Abdulrahman Aldhuhayan; Abdulrahman AlAbdulkarim; Bader Fatani; Abdulaziz Alabood (Elsevier, 2024)
Background: The kidneys carry out many essential processes. A reduced glomerular filtration rate is the primary cause of renal failure. Patients with chronic kidney disease are significantly increasing all around the world. Patients with varying degrees of renal disease will be seen on the dental chair, and the dentist must be aware of dental considerations when treating such patient. Dental clinicians should carefully evaluate the oral findings and general condition of the renal disease patient. Objective: To increase the awareness of dentists in the dental management of patients with renal diseases or undergoing renal transplant. Methods: This study reviews 56 articles searched on two databases PubMed and Google Scholar with English language. Conclusion: Every dentist should be well-informed regarding dental considerations and oral manifestations when treating a patient with any renal disease. Simple treatment plan modification can prevent the evolution of mild to critical medical or dental complications in renal disease patients.